2017
DOI: 10.1007/s12094-017-1807-y
|View full text |Cite
|
Sign up to set email alerts
|

SEOM clinical guideline on unknown primary cancer (2017)

Abstract: Cancer of unknown primary site is a histologically confirmed cancer that manifests in advanced stage, with no identifiable primary site following standard diagnostic procedures. Patients are initially categorized based on the findings of the initial biopsy: adenocarcinoma, squamous-cell carcinoma, neuroendocrine carcinoma, and poorly differentiated carcinoma. Appropriate patient management requires understanding several clinical and pathological features that aid in identifying several subsets of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 29 publications
0
69
0
2
Order By: Relevance
“…However, in another study (GEFCAPI 04), where gene expression analysis was used to identify the most likely primary tumor, the best available targeted therapy and other treatments tailored to the primary tumor failed to improve disease progression or survival compared with chemotherapy [32]. For cancers of unknown primary origin taxanes are recognized as a chemotherapeutic option, so cabazitaxel could be a useful treatment option to be studied in these patients that have resistance to docetaxel [33,34]. Furthermore, it has been shown that patients with some specific subtypes of prostate cancer, such as luminal B (classified using gene expression signatures) experience significant improvements in time to castration resistance and overall survival following treatment with docetaxel plus androgen deprivation therapy (ADT) [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study (GEFCAPI 04), where gene expression analysis was used to identify the most likely primary tumor, the best available targeted therapy and other treatments tailored to the primary tumor failed to improve disease progression or survival compared with chemotherapy [32]. For cancers of unknown primary origin taxanes are recognized as a chemotherapeutic option, so cabazitaxel could be a useful treatment option to be studied in these patients that have resistance to docetaxel [33,34]. Furthermore, it has been shown that patients with some specific subtypes of prostate cancer, such as luminal B (classified using gene expression signatures) experience significant improvements in time to castration resistance and overall survival following treatment with docetaxel plus androgen deprivation therapy (ADT) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Then, IHC is further employed in order to identify the primary site. The most commonly added proteins to the IHC CUP staining panel are the keratin family members; CK7 and CK20, with the CK7 + /CK20being the most common in CUP (CK7 + /CK20 -Breast, Ovarian, Pulmonary, Endometrial, Thyroid; CK7 + /CK20 + Upper gastrointestinal, Pancreatic, Urothelial; CK7 -/CK20 + Colorectal, Merkel cell; CK7 -/CK20 -Prostatic, Hepatocellular, Renal cell, and Adrenal cortical) [23]. Other cytoplasmic markers that are commonly added to the IHC staining panels also include; SCGB2A2 and GCDFP-15; breast origin, TTF-1; lung origin, HepPar-1; liver origin, RCC and PSA; renal and prostate origin respectively [24].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…CUP is a kind of advanced cancer in which the primary site cannot be determined after the standard diagnostic procedure. It is diagnosed by histological examination primarily, and the patients are preliminarily classified as well or moderately differentiated adenocarcinomas (60%), squamous‐cell carcinomas (5%), carcinomas with neuroendocrine differentiation (1%), poorly differentiated carcinomas (25%–30%), and undifferentiated neoplasm (5%) according to the findings of the first biopsy . Because the location of the primary focus is unclear, site‐specific first‐line therapy cannot be applied; thus, currently, for the treatment of CUP, broad‐spectrum chemotherapy drugs, such as paclitaxel or gemcitabine combined with platinum, are usually used.…”
Section: Introductionmentioning
confidence: 99%